Molecular Typing of Dengue Virus Circulating in Kolkata, India in 2010 - Arindam Sarkar; Debjani Taraphdar; Shyamalendu Chatterjee (Journal of Tropical Medicine)
Dengue is one of the major public health threats in Kolkata. Every year, blood samples with dengue-like illness are referred to us from different medical colleges and hospitals in Kolkata for the detection of dengue infection in them. In 2010, a total of 378 samples were referred to us for that purpose. All the samples were tested for the detection of IgM antibodies by ELISA method, followed by RT-PCR test for the detection of serotypes. Only 173 samples were ELISA positive. Out of 378 samples, 108 were RT-PCR positive. Out of 108 samples, 74 samples had monotypic infection with different serotypes of DENV and 33 samples had dual infections with DENV-2 and DENV-3. Only one sample had the infection with DENV-1, DENV-2, and DENV-3. DHF was found mainly among the patients, infected with multiple dengue serotypes. Only 3 dengue monotypic infected patients had suffered from DHF.